(untitled) (Journal of Enam Medical College, 2021)
Evans syndrome is an uncommon haematological disorder characterised by autoimmune haemolytic anaemia (AIHA), immune thrombocytopenia (ITP) and/or immune neutropenia. It may occur in all ethnic groups, all ages and has no sex predilection. The direct antiglobulin test (DAT) is almost invariably positive. This condition generally runs a chronic course and is characterised by frequent exacerbations and remissions. Corticosteroids and/or intravenous immunoglobulin (IVIG) are the most commonly used first line therapy. Here we report a case of a female who presented with severe shortness of breath, palpitation and low grade fever and on examination she was found severely pale and mildly icteric. Her CBC and PBF showed pancytopenia. Indirect bilirubin and LDH were raised and direct Coomb’s test was positive. She was labeled as a case of Evans syndrome and responded to oral prednisolone. On subsequent follow-up her haematological profiles remained normal. J Enam Med Col 2020; 10(2): 114-117